2022
DOI: 10.3390/sym14030497
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of a Unified Methodology for Assessing the Resource Efficiency of International Digital Platform Promotion for E-Learning

Abstract: Ideas related to the systematization of educational technologies are of great interest. This is due, among other things, to the principles of symmetry. On the basis of their application, the synthesis of well-established facts and principles in international education will be realized. Practical needs that are directed towards the future will also be realized. This paper is devoted to the study and creation of a methodology that makes it possible to evaluate the resource efficiency of an interethnic digital pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The methods dedicated to the problem of resource allocation are based on three fundamental principles of allocation: proportional, optimal, and inverse priorities [36,37]. These methods present significant disadvantages that can be treated through the application of the < XR > approach to maximize various positive consequences and minimize the negative consequences associated with the allocation of resources, considering or not considering the presence of deficiencies [6,38].…”
Section: Problem Statementmentioning
confidence: 99%
“…The methods dedicated to the problem of resource allocation are based on three fundamental principles of allocation: proportional, optimal, and inverse priorities [36,37]. These methods present significant disadvantages that can be treated through the application of the < XR > approach to maximize various positive consequences and minimize the negative consequences associated with the allocation of resources, considering or not considering the presence of deficiencies [6,38].…”
Section: Problem Statementmentioning
confidence: 99%
“…It was found that it is possible that, as Industry 4.0 develops, soft skills will become more and more crucial, and also that teaching them is far more difficult and time consuming. The difference between the proposed tool and existing tools is that it includes the opportunity to express preferences regarding the abilities to be utilised and improved [12,13].…”
Section: Literature Review: Relevant Landscape-resource Efficiency Ma...mentioning
confidence: 99%